Treatment of spontaneous preterm labour with retosiban: a phase II pilot dose‐ranging study. (11th July 2017) - Thornton, Steven; Valenzuela, Guillermo; Baidoo, Charlotte; Fossler, Michael J.; Montague, Timothy H.; Clayton, Linda; Powell, Marcy; Snidow, Jerry; Stier, Brendt; Soergel, David
Abstract : Aims: The aims of the present study were to investigate the maternal, fetal and neonatal safety and tolerability, pharmacodynamics and pharmacokinetics of intravenous (IV) retosiban in pregnant women with spontaneous preterm labour (PTL) between 34 0/7 and 35 6/7 weeks' gestation. Methods: In parts A and B of a three‐part, double‐blind, placebo‐controlled, multicentre study, women were randomized 3:1 (Part A) or 2:1 (Part B) to either 12‐h IV retosiban followed by a single dose of oral placebo (R‐P) or 12‐h IV placebo followed by single‐dose oral retosiban (P‐R). Results: A total of 29 women were randomized; 20 to R‐P and nine to P‐R. An integrated analysis found that adverse events were infrequent in mothers/newborns and consistent with events expected in the population under study or associated with confounding factors. Retosiban was rapidly absorbed after oral administration, with an observed half‐life of 1.45 h. Efficacy analyses included 19 women. While not statistically significant, those receiving R‐P more frequently achieved uterine quiescence in 6 h (R‐P, 63%; 95% credible interval [CrI]: 38, 84; P‐R, 43%; 95% CrI: 12, 78) and more achieved a reduction of ≥50% in uterine contractions in 6 h (R‐P, 63%; 95% CrI: 38, 84; P‐R, 29%; 95% CrI: 4, 64). The number of days to delivery was increased in women receiving R‐P (median 26 days for R‐P vs. 13 days for P‐R). Conclusions: Intravenous retosiban has a favourable safety and tolerability profile and might prolong pregnancies in women with PTL. The study provides the rationale and dosing strategy for further evaluation of the efficacy of retosiban in the treatment of PTL.